2020
DOI: 10.1111/pai.13330
|View full text |Cite
|
Sign up to set email alerts
|

Behind the scene: Paracetamol hypersensitivity in children

Abstract: Background: Paracetamol, a non-steroidal anti-inflammatory drug, is commonly being used for fever and pain relief worldwide. The aim of this study was to evaluate children with a suspected history of paracetamol hypersensitivity. Methods: Sixty patients who were referred to our clinic in between January 2015 and December 2018 with a suspected history of paracetamol hypersensitivity were included. Reactions were classified according to the European Network for Drug Allergy (ENDA)/Global Allergy and Asthma Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
(101 reference statements)
1
8
0
Order By: Relevance
“…In patients with a positive history of paracetamol-induced hypersensitivity reactions, we performed skin tests that were negative. This is in accordance with the studies published by Sipahi Cimen et al who reported only one positive skin test to paracetamol, but the patient tolerated the OPT with paracetamol [16]. The negative skin tests to paracetamol suggest that the mechanisms that underlie acetaminophen hypersensitivity are not IgE-mediated.…”
Section: Discussionsupporting
confidence: 92%
“…In patients with a positive history of paracetamol-induced hypersensitivity reactions, we performed skin tests that were negative. This is in accordance with the studies published by Sipahi Cimen et al who reported only one positive skin test to paracetamol, but the patient tolerated the OPT with paracetamol [16]. The negative skin tests to paracetamol suggest that the mechanisms that underlie acetaminophen hypersensitivity are not IgE-mediated.…”
Section: Discussionsupporting
confidence: 92%
“…The rate of NSAID-H, as confirmed with oral provocation tests (OPT), was measured between 4% and 68% in various patient groups with histories of suspected reactions (Table 2). 25,27,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Considering the general pediatric population, the rate of actual ASA-hypersensitivity (ASA-H) in 1632 control subjects was detected as 0.55% according to the OPT performed independent of suspected ASA-H history. 45 However, in a very recent study in which OPT with ASA was performed Alves, 2017 35 119, NSAID-induced 5-14 y NSAID-H NA OPT w culprit and alternative drug 7.6% Arikoglu, 2017 36 106, NSAID-induced if there was a positive clinical history, only one participant had undergone OPT, and no ASA-H was detected in 2000 control subjects (Table 2).…”
Section: The Impact Of Nsaid-h In the Pediatric Populationmentioning
confidence: 99%
“…25,31,38 The rate of OPT-proven paracetamol hypersensitivity was 13% in children and adolescents with a suspected reaction in their history. 42 In a recent meta-analysis, the prevalence of OPTproven paracetamol hypersensitivity was reported as 10.1%, with a 95% confidence interval of 4.5 to 15.5%. 65 NSAID-H tends to persist for years.…”
Section: The Impact Of Nsaid-h In the Pediatric Populationmentioning
confidence: 99%
“…17 It is known that drug allergy may be generally overestimated in children and a suspected history of drug allergy needs to be confirmed by detailed allergy work-up. 18 Our results showed that 94.4%…”
Section: Skin Test Resultsmentioning
confidence: 58%
“…It is known that drug allergy may be generally overestimated in children and a suspected history of drug allergy needs to be confirmed by detailed allergy work‐up 18 . Our results showed that 94.4% of study patients with a suspected history of CLR‐HRs could in fact tolerate this antibiotic.…”
Section: Discussionmentioning
confidence: 67%